Stress, adaptation, and nitric oxide - Malyshev, Y.; Manukhina, E. B. (Biokhimiya, 1998)
The biological role of nitric oxide (NO) has been studied for more than ten years. Nevertheless, the number of investigations in this field continues to increase. It is now suggested that NO is a previously unrecognized, very important regulator of physiological functions and cell metabolism in the body. Through the application of the methods of molecular biology, more and more data are being accumulated on the regulatory role of NO in the mechanism of gene expression and protein biosynthesis. The data presented in this review show an important role of NO in stress and adaptive responses of organisms and thereby expand existing notions on the biological role of this unique molecule. This review substantiates the idea that the system of NO generation is a newly discovered stress-limiting system. The action of this NO-ergic system is based on the capability of NO to limit key links of the stress reaction and to enhance the potency of endogenous defense systems of the organism. The role of NO is considered at the major stages of adaptation: 1) at the urgent stage related with the stress reaction; 2) at the stage of the transition from urgent to long-term adaptation; and 3) at the stage of long-term adaptation characterized by the formation of stable protective effects. It is demonstrated that pharmacological "imitation" of the activated NO-ergic system by administration of NO donors to the organism provides in many instances an efficient protection against stress damage and enhances the adaptive capacity of the organism.